2019
DOI: 10.1016/j.csbj.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Computational Simulations Identified Two Candidate Inhibitors of Cdk5/p25 to Abrogate Tau-associated Neurological Disorders

Abstract: Deregulation of Cdk5 is a hallmark in neurodegenerative diseases and its complex with p25 forms Cdk5/p25, thereby causes severe neuropathological insults. Cdk5/p25 abnormally phosphorylates tau protein, and induces tau-associated neurofibrillary tangles in neurological disorders. Therefore, the pharmacological inhibition of Cdk5/p25 alleviates tau-associated neurological disorders. Herein, computational simulations probed two candidate inhibitors of Cdk5/p25. Structure-based pharmacophore investigated the esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 58 publications
3
17
0
Order By: Relevance
“…A group of marine indole alkaloids isolated from the marine tunicate Aplidium were identified as scaffolds for designing new anti-Tau hyperphosphorylation inhibitors using docking and MD simulations [149]. Docking calculation followed by MD simulations and binding free energy analysis led to the identification of novel anti-Tau hyperphosphorylation inhibitors of Cdk5 which occupied the ATP-binding site of the enzyme [150]. A set of pyrazolopyrimidine derivatives, which are inhibitors of GSK3β, were studied with docking calculations and 3D-QSAR to develop reliable predictive models for design new compounds to inhibit Tau hyperphosphorylation [151].…”
Section: Cadd For the Development Of Anti-tau Inhibitorsmentioning
confidence: 99%
“…A group of marine indole alkaloids isolated from the marine tunicate Aplidium were identified as scaffolds for designing new anti-Tau hyperphosphorylation inhibitors using docking and MD simulations [149]. Docking calculation followed by MD simulations and binding free energy analysis led to the identification of novel anti-Tau hyperphosphorylation inhibitors of Cdk5 which occupied the ATP-binding site of the enzyme [150]. A set of pyrazolopyrimidine derivatives, which are inhibitors of GSK3β, were studied with docking calculations and 3D-QSAR to develop reliable predictive models for design new compounds to inhibit Tau hyperphosphorylation [151].…”
Section: Cadd For the Development Of Anti-tau Inhibitorsmentioning
confidence: 99%
“…Unlike other CDKs that require the binding of cyclins in order for their activation, CDK5 requires the binding of p35, p39, or p25 (a proteolytic fragment of p35) for activation. p35 (NCK5a, neuronal CDK5 activator) was first discovered due to its association and activation of CDK5 [17][18][19]. However, p39 (NCK5ai, neuronal CDK5 activator isoform) was first identified as a 39 kDa isoform of p35 that shared 57% amino acid homology with p35 [20], p25 was first discovered as a truncated form of p35 that was found in the neurons of Alzheimer patients [21], and subsequent studies identified that cleavage of p35 into p25 was calpain-and dephosphorylation-dependent [22][23][24].…”
Section: Activators Of Cdk5mentioning
confidence: 99%
“…The proteolytic p25 fragment of p35 exhibits a different subcellular localization with and is more stable that its precursor p35. CDK5/p25 have shown to phosphorylate both Tau and MAP1B found in neurofibrillary tangles (NFTs) compared with CDK5/p35 [19,31]. CDK5 has been shown to have various roles in synapse formation, maintenance, and synaptic communication.…”
Section: Function Of Cdk5 In Neuronal Developmentmentioning
confidence: 99%
“…The system was simulated for 100 ns using the Amber 99sb force field ( Sakkiah et al, 2018 ) and the TIP3P water model ( Lim et al, 2019 ). The free binding energy between NDM-1 and the ligand was calculated by the Molecular Mechanics/Generalized Born Surface Area (MM-GBSA) method ( Liu et al, 2018b ; Zeb et al, 2019 ; Nie et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%